S-MFAC Control of Posture and Position Tracking for Working-class ROV - QIAO Yuekun; ZHU Yinggu; YAN Yun; LUO Lingbo; HU Binwei (Kongzhi Yu Xinxi Jishu)
In considering the frequent variation of model parameters, complicated operating environment, numerous uncertain factors and strong nonlinearity of motion in working-class ROV(remotely operation vehicle), this paper presented an S-MFAC (sigmoid-model free adaptive control) nonlinear cascade control algorithm. The outer loop of the algorithm uses the bounded, smoothing output characteristics of S-MFAC to convert the instruction of posture and position into smooth inner loop reference speed to satisfy the actuator constraints, and the inner loop controller uses MFAC to eliminate the disturbance factors in the ROV system. Stable and accurate tracking closed-loop control is realized for each degree of freedom. Control effectiveness of the algorithm in velocity tracking and 3D trajectory tracking was verified by building a simulation model. The results shows that the S-MFAC control algorithm has better dynamic control effect than the PID algorithm under the same condition without ROV precise mathematical model. In addition, the control algorithm can reduce the workload of the navigator due to the optimization of the operation input.